1970
DOI: 10.1021/jf60168a031
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of residues from atrazine, ametryne, and pentachlorophenol in sugarcane

Abstract: Atrazine, ametryne, and PCP, all labeled with 14C, were applied to sugarcane and the movement of radioactivity in the plant was followed to determine the fate of their residues. Atrazine-14C and PCP-14C, applied to sugarcane leaf blades, remained at the site of treatment, but with substantial losses of radioactivity. As the leaves naturally abscised, all radioactivity was lost from the plant. applied in nutrient solution to roots of growing plants was absorbed by the roots and did not trans-locate. With time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It has been amply documented that the basis of selectivity of atrazine in tolerant crops, such as corn, sorghum, and sugar cane is the ability to biochemically degrade the herbicide to nontoxic metabolites (7,8,11,19,21,23,25). This ability is also shared by a number of grass weed species that are increas ing in importance in com growing areas where atrazine has been used repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…It has been amply documented that the basis of selectivity of atrazine in tolerant crops, such as corn, sorghum, and sugar cane is the ability to biochemically degrade the herbicide to nontoxic metabolites (7,8,11,19,21,23,25). This ability is also shared by a number of grass weed species that are increas ing in importance in com growing areas where atrazine has been used repeatedly.…”
Section: Introductionmentioning
confidence: 99%
“…The measured loss of unidentified metabolite and 14C02 from the sugarcane shoot and the substantial loss of 14C02 from the soil/root system (4% of applied 14C) probably explain the low recoveries reported by Hilton et al (1970). The presence of a metabolite from ametryne in the transpired/guttated water from sugarcane indicates an additional, hitherto unreported mechanism by which a pesticide metabolite may be lost from plants.…”
Section: Resultsmentioning
confidence: 95%
“…Most studies have been conducted with the chloros-triazines. The only specific study on ametryne degradation in sugarcane (Hilton et al, 1970) suggested absence of ametryne and hydroxyametryne (equivalent to hydroxyatrazine, 2-ethylamino-4-isopropylamino-6-hydroxy-s-triazine) in the leaf and root extracts, while more than half of the applied ametryne (ring-14C) remained unaccounted for at 13 weeks. It appears that a large proportion of the 14C disappeared, possibly in some volatile form.…”
mentioning
confidence: 99%
“…PCP and its sodium salt (Na‐PCP) are commonly used as bactericides, fungicides, herbicides, algaecides, defoliants, and wood preservatives (Ge et al., 2007; Gulcan et al., 2008; Hilton et al., 1970; Lamparski et al., 1978; Li et al., 2012; Piskorska‐Pliszczynska et al., 2016; Ryan et al., 1985; Tang et al., 2007; Xiao et al., 2012; Zheng et al., 2011; Zhou et al., 2017). In particular, they were extensively sprayed in the aquatic system in southern China from the early 1960s to the early 1990s to kill snails, which are the intermediate hosts of schistosomes, for schistosomiasis control (Hong et al., 2005; Tang et al., 2007; Xiao et al., 2012; Zheng et al., 2012; Zhou et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ubiquitous and persistent nature in animals and animal source foods, PCP can easily accumulate at high levels in environmental media, contaminated feeds, and wood elements of farm facilities treated with PCP (Ge et al., 2007; Ryan et al., 1985). Substantial studies have been published on the occurrence of PCP in foods, including highly sensitive analytical methods for detection (Faas & Moore, 1979; Farrington & Munday, 1976; Lamparski et al., 1978; Stark, 1969; Zhao, 2013), contamination levels of PCP in aquatic, livestock, poultry, and dairy products (Fernandes et al., 2019; Ge et al., 2007; Lamparski et al., 1978; Ryan et al., 1985), and the fate of PCP residue from environmental media to animal derived foods (Faas & Moore, 1979) and plant origins (Hilton et al., 1970). Furthermore, human biological samples, such as blood plasma, cord blood plasma, and breast milk, have been analyzed to investigate internal exposure levels to PCP (Guvenius et al., 2003; Hong et al., 2005).…”
Section: Introductionmentioning
confidence: 99%